PERBEDAAN PENERAPAN MODEL PEMBELAJARAN PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE DAN PEMBELAJARAN KONVENSIONAL PADA KELAS VII SMP NEGERI 10 SAMARINDA - Hanifah Eka Wati (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
The purpose of this study was to determine the differences between students' mathematics learning outcomes by type of cooperative learning think-pair-share and conventional learning on the subject of arithmetic operations in the algebra of class VII SMP Negeri 10 Samarinda. The study was conducted in SMP Negeri 10 Samarinda, the population of all students of class VII. This research is quasi-experimental. The sampling technique used in this research is the purpose cluster sampling. This research sample there are two classes, VIID as an experimental class (40 students), class of cooperative learning by think-pair-share and class VIIa as a control class (40 students), class by learning konvensional.Instrumen used in this study is a written test (initial test and final test). The conclusion that there are differences in mathematics between student learning outcomes by type of cooperative learning think-pair-share and conventional learning on the subject of arithmetic operations in the algebra of class VII SMP 10. The results of mathematical learning using cooperative learning model of think-pair- better share when compared with the results of mathematical learning using conventional learning models.Keywords: Learning Model, Think-Pair-Share, Conventional and learning outcomes